2017
DOI: 10.1111/inm.12340
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcomes of patients presenting to an adult emergency department involuntarily with substance misuse

Abstract: Alcohol and other drug (AOD) use is common in our society. The use of these substances flow throughout all areas of healthcare, and is especially prevalent in patients presenting to the emergency department with signs of mental illness. At the extreme end of these presentations patients present involuntarily with either police or ambulance officers. The aim of this study was to identify and describe the population presenting to the ED involuntarily with and without substance misuse as a precipitating factor. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While there are several possible reasons for people BIBP being triaged as a higher urgency in 9 comparison to the general ED population, previous research has shown that substance misuse is high in this group [5,9]. Substance misuse is linked to more urgent triage categories [19] and the need for specialised care, which is often beyond the standard training and capability of ED nursing staff [20]. As a result, additional nursing staff are often required and an increased LOS in the ED is incurred [21].…”
Section: Discussionmentioning
confidence: 94%
“…While there are several possible reasons for people BIBP being triaged as a higher urgency in 9 comparison to the general ED population, previous research has shown that substance misuse is high in this group [5,9]. Substance misuse is linked to more urgent triage categories [19] and the need for specialised care, which is often beyond the standard training and capability of ED nursing staff [20]. As a result, additional nursing staff are often required and an increased LOS in the ED is incurred [21].…”
Section: Discussionmentioning
confidence: 94%